A National Survey of Critical Care Physicians' Knowledge, Attitudes, and Perceptions of Antimicrobial Stewardship Programs. (January 2016) - Steinberg, Marilyn; Dresser, Linda D.; Daneman, Nick; Smith, Orla M.; Matte, Andrea; Marinoff, Nicole; Bell, Chaim M.; Morris, Andrew M.
Objective: Antimicrobial stewardship is a process designed to optimize antimicrobial therapy by ensuring patients get the right antimicrobials at the right dose and at the right time. Antimicrobial stewardship programs (ASPs) are increasingly being implemented in health care institutions, are required by some accreditation bodies, and have the potential for maximum impact in intensive care units (ICUs). We administered a survey to critical care physicians across Canada to better understand their knowledge, attitudes, and perceptions on the utility of ASPs in improving patient care. Design, Setting, and Patients: We distributed a Web-based survey to physicians who attend in Canadian ICUs. Respondents were identified through the membership lists of multiple critical care organizations. Content validity, utility, clarity, and test–retest reliability were evaluated prior to distribution. Survey items assessed ASP knowledge, attitudes, and experiences. Attitudes toward ASPs were assessed on a 5-point Likert-type scale. Measurements and Main Results: The survey was completed by 185 physicians, with a response rate of 29% (n = 185/634) for all physicians contacted. A majority (74%) of respondents reported that there was at least 1 component of an ASP at their institution. Most (86%) respondents agreed or strongly agreed that the patients in their ICU benefit from an ASP, with 81% reporting the ASP increases their knowledge of appropriate antimicrobial use in the ICU setting. Only 11% of respondents reported they felt that time spent interacting with the ASP team was an inefficient use of their time, and only 7% expressed concern that the ASP negatively affected their autonomy. Conclusion: Based on our survey results, Canadian intensivists are supportive of antimicrobial stewardship in ICUs and feel that ASPs provide a valuable service to both patients and clinicians.